SEDEKAH HIJAU BERBASIS HADIS DALAM PENGHIJAUAN PARTISIPATIF MAHASISWA PKN IIM SURAKARTA DI KALINCAR - Ngatmin Abbas; M. Fatchurroman; Dudi Budi Astoko (LPPM STAI Muhammadiyah Probolinggo, 2026)
The escalating environmental degradation requires active involvement from all societal elements, including Islamic higher education institutions. This article examines a community service program of tree planting conducted on February 8, 2026 in Kalincar Subdistrict, Selogiri, Wonogiri Regency. The activity engaged a Field Supervisor and students from the Islamic Education (PAI) and Elementary Teacher Education (PGMI) departments of Institut Islam Mamba’ul ‘Ulum (IIM) Surakarta in a participatory-educative greening action. The implementation method prioritized active community involvement and the integration of Islamic values, in line with a participatory educational approach. The results show that 20 tree seedlings (of gayam, matoa, tabebuia, and glodokan species) were planted with enthusiastic participation of local residents. The community not only benefited from a greener environment, but also gained ecological education grounded in Islamic teachings, such as hadiths on planting trees and the concept of humans as stewards of the earth. The public response was very positive and appreciative, as evidenced by strong support and commitment to care for the planted trees. The integration of Islamic values such as the divine trust (amanah) to protect nature and the spirit of ongoing charity (sadaqah jariyah) through planting strengthened environmental character building for both students and residents. In conclusion, this Islamic values-based greening program effectively raised ecological awareness and built a campus-community partnership in environmental conservation. Similar activities are recommended to be continuously developed as a form of Islamic higher education’s contribution to addressing environmental crises. Keywords: Community service; Reforestation; Islamic values; Environment